2019
DOI: 10.3389/fcimb.2019.00237
|View full text |Cite
|
Sign up to set email alerts
|

The Paradoxical Leishmanicidal Effects of Superoxide Dismutase (SOD)-Mimetic Tempol in Leishmania braziliensis Infection in vitro

Abstract: Leishmaniasis is an infectious disease caused by protozoans of the genus Leishmania . The macrophage is the resident cell in which the parasite replicates and it is important to identify new compounds that can aid in parasite elimination since the drugs used to treat leishmaniasis are toxic and present side effects. We have previously shown that treatment of Leishmania braziliensis -infected macrophages with DETC (Diethyldithiocarbamate) induces parasite killing, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 37 publications
0
7
0
Order By: Relevance
“…braziliensis amastigotes survive and replicate much better in the absence of ROS, identifying these molecules as important regulators of the parasite proliferation inside the host cells [ 48 ]. In addition, supplementation of cell cultures with pro-oxidants and antioxidants modulates Leishmania infection, resulting in a reduced parasite load in stressful conditions [ 49 ]. Moreover, sensitivity to distinct reactive species may vary in the parasite stages, with H 2 O 2 being more toxic to Leishmania amastigotes than O 2 •− [ 43 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…braziliensis amastigotes survive and replicate much better in the absence of ROS, identifying these molecules as important regulators of the parasite proliferation inside the host cells [ 48 ]. In addition, supplementation of cell cultures with pro-oxidants and antioxidants modulates Leishmania infection, resulting in a reduced parasite load in stressful conditions [ 49 ]. Moreover, sensitivity to distinct reactive species may vary in the parasite stages, with H 2 O 2 being more toxic to Leishmania amastigotes than O 2 •− [ 43 , 50 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, O 2 •− metabolism might be essential for NO-resistant strain because only SOD-treated cells showed reduction in the parasite load. The use of tempol, an antioxidant able to promote O 2 •− dismutation at rates similar to SOD, pointed to the dual role of this free radical to control the infection, highlighting differences in the pathogenesis of cutaneous leishmaniasis caused by different species of Leishmania [ 49 , 51 , 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…TEMPOL exhibited strong antiviral activity at concentrations above 0.2 mM. Viral titers were reduced by more than 5 log 10 in the presence of 0.4 mM TEMPOL, which is reported to have a 50% cytotoxic concentration (CC50) greater than 100 mM (50). Our studies present a molecular basis for pursuing TEMPOLwith its low cytotoxicity and known access to tissues relevant for COVID-19 infection (51, 52)-and other related stable nitroxides as potential SARS-CoV-2 therapies during active viral infection.…”
mentioning
confidence: 99%
“…The first study to evaluate the role of HO-1 on leishmaniasis, using L. mexicana pifanoi, showed that amastigotes induce high HO-1 expression early after macrophage infection [55]. Inhibition of HO-1 activity with SnPPIX increased ROS production after amastigote phagocytosis, while induction of HO-1 with CoPPIX reduced the amounts of superoxide, an important ROS associated to Leishmania control inside macrophages [101]. However, these authors did not study the effects of manipulating HO-1 on parasite burden.…”
Section: Ho-1 In Leishmaniasismentioning
confidence: 99%